City As Landscape : A Post Post-Modern View of Design and Planning. - Turner, Tom (CRC Press LLC, 1995)
In twenty essays, this book covers aspects of planning, architecture, urban design, landscape architecture, park and garden design. Their approach, described as post-postmodern, is a challenge to the 'anything goes' eclecticism of the merely postmodern.